A proteasome inhibitor prevents activation of NF-kappa B and stabilizes a newly phosphorylated form of I kappa B-alpha that is still bound to NF-kappa B. - Traenckner, E B (1994)
Activation of the inducible transcription factor NF-kappa B involves removal of the inhibitory subunit I kappa B-alpha from a latent cytoplasmic complex. It has been reported that I kappa B-alpha is subject to both phosphorylation and proteolysis in the process of NF-kappa B activation. In this study, we present evidence that the multicatalytic cytosolic protease (proteasome) is involved in the degradation of I kappa B-alpha. Micromolar amounts of the peptide Cbz-Ile-Glu(O-t-Bu)-Ala-leucinal (PSI), a specific inhibitor of the chymotrypsin-like activity of the proteasome, prevented activation of NF-kappa B in response to tumor necrosis factor-alpha (TNF) and okadaic acid (OA) through inhibition of I kappa B-alpha degradation. The m-calpain inhibitor Cbz-Leu-leucinal was ineffective. In the presence of PSI, a newly phosphorylated form of I kappa B-alpha accumulated in TNF- and OA-stimulated cells. However, the covalent modification of I kappa B-alpha was not sufficient for activation of NF-kappa B: no substantial NF-kappa B DNA binding activity appeared in cells because the newly phosphorylated form of I kappa B-alpha was still tightly bound to p65 NF-kappa B. Pyrrolidinedithiocarbamate, an antioxidant inhibitor of NF-kappa B activation which did not interfere with proteasome activities, prevented de novo phosphorylation of I kappa B-alpha as well as its subsequent degradation. This suggests that phosphorylation of I kappa B-alpha is equally necessary for the activation of NF-kappa B.(ABSTRACT TRUNCATED AT 250 WORDS)